Psychoeducation through digital video for Olympic and Paralympic athletic career transition - Burrows, E.; McArdle, S. (Health Education Journal, 2019)
Objective: Prior research has noted Olympic and Paralympic athletes are often unaware and unprepared for upcoming career transitions, resulting in experiences of psychological distress. The purpose of this study was to explore the use of digital video as a delivery method for psychoeducation about an upcoming career transition.